Clinical characteristics and prognosis of anti-γ-aminobutyric acid-B receptor encephalitis: A single-center, longitudinal study in China - Feng, Xuedan; Zhang, Yujing; Gao, Yu; Zhang, Jing; Yu, Shasha; Lv, Jing; Zu, Yu; Wang, Lin; Wang, Xiangbo (Frontiers in Neurology, 2022)
Objective Anti-γ-aminobutyric acid-B receptor (GABABR) encephalitis is a rare type of autoimmune encephalitis. There are only a few, small, published studies regarding prognosis, so prediction of prognosis is of limited accuracy. We identified 37 cases of anti-GABABR encephalitis in China. Here, we present these patients' clinical characteristics and long-term outcomes. Methods We collected and retrospectively analyzed the clinical data of 37 patients with anti-GABABR encephalitis from Beijing Fengtai You'anmen Hospital. Results The study cohort comprised 37 patients of anti-GABABR encephalitis of median age 61 years (range: 11–77), 28 of whom were male. The main clinical manifestations were epilepsy (91.9%, 34/37), psychiatric disorders (94.6%, 35/37) and cognitive impairment (97.3%, 36/37). Tumors were identified in 18 (48.6%) patients. First-line immunotherapy was administered to 34 patients, 31 of whom (90.6%) responded favorably. During a median follow-up of 18 months (range: 1–72 months), 21 patients had good outcomes [Modified Ranking Scale (mRS ≤2)], 16 (43.2%) died (mRS 6), and 7 (18.9%) relapsed. Age (P = 0.005), disturbance of consciousness (P = 0.018), admission to the Neurology Intensive Care Unit (P = 0.003), mechanical ventilation (P = 0.009), more numerous clinical manifestations (P = 0.008), comorbid malignancy (P = 0.008), multiple anti-neuronal antibodies (P = 0.029), and hyponatremia (P = 0.023) differed significantly between patients with good outcomes (mRS 0–2) and those with poor outcomes (mRS 3–6). Conclusion Men aged 50–70 years accounted for most of the patients with anti-GABABR encephalitis in our case series. The main clinical manifestations were epilepsy and neuropsychiatric dysfunction. The participants often had concomitant lung cancer, particularly small-cell lung cancer. Patients with lung tumors and/or serious manifestations usually had a poor prognosis with high mortality. Early identification and treatment of tumors improved the poor prognosis to some extent.